The challenges of mathematizing in Swedish early childhood education - Camilla Björklund; Hanna Palmér (Journal of Early Childhood Education Research, 2024)
Even though there today is a solid view on early childhood mathematics education being of importance, there is a quite diverse view on how this education is to be realized. In many countries, both teaching and play are emphasized in the early childhood education curricula why the question of how to conduct play-oriented mathematics education is relevant. In this study, we empirically elaborate on mathematizing as a possible cross between play and mathematics education. Mathematizing, as developed by the Dutch mathematician Hans Freudenthal, implies seeing the world in the light of mathematics and being able to identify how mathematics contribute to solving everyday problems. In this study we empirically investigate the theoretical construct of mathematizing in a preschool setting, aiming to clarify when and how mathematizing is made possible, and what seem to be the constraints on it. Based on 15 observations of preschool teachers’ attempts to implement play-oriented mathematics education, the presence of a true problem and character of teachers’ questions stand out as the keys to making mathematizing, as a merge of play and teaching, possible.